Origins of the Monitoring, Evaluation and Learning, Communities of Practice (CoP) & Task Force on Indicators - CGIAR Indicator Task Force (CGIAR Indicator Task Force, 2016)
Origins of the Monitoring, Evaluation and Learning, Communities of Practice (CoP) & Task Force on Indicators.